ANALISIS EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA SUPERMARKET PARAGON MART TAHUNA - Kalendesang, Angelina Klesia; Lambey, Linda; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Internal control of the inventory of goods is critical in protecting the company's assets from fraud, misappropriation, errors of record and damage that may occur and be committed by employees or other parties. Therefore, the internal control system must be run effectively in order to avoid cheating, fraud and errors. The purpose of this research is to analyze the effectiveness of internal inventory control system at Paragon Mart Tahuna Supermarket. The analytical method used was qualitative by observations and direct interview with the Owner and some of employees at Paragon Mart. The results show that the internal control of merchandise inventory at Paragon Mart is already effective, they were monitoring and checking their inventory on a daily basis. In addition, every task should be distributed evenly among the employees for clearer tasks and responsibilities to increase the effectiveness of controlling and monitoring function.Keywords : Effectiveness, Internal Control System, Inventory